2016
DOI: 10.19159/tutad.34726
|View full text |Cite
|
Sign up to set email alerts
|

İzmir İli kiraz bahçelerinde bulunan Saydam ağustosböceği [Cicadatra hyalina (Fabricius, 1798) (Hemiptera: Cicadidae)’nin yayılışı ile morfolojik ve biyolojik bazı özellikleri üzerinde araştırmalar

Abstract: Özet: Bu çalışma, İzmir ili kiraz bahçelerinde bulunan Saydam ağustosböceği, Cicadatra hyalina (Fabricius, 1798) (Hemiptera: Cicadidae)'nın yayılışını, bazı morfolojik özelliklerini ve doğadaki biyoekolojisini belirlemek amacıyla 2005-2008 yıllarında yürütülmüştür. Yayılışını belirlemek için İzmir'in 17 ilçesindeki 98 bahçede gözlem yapılmıştır. Biyolojisi ile ilgili gözlemler Kemalpaşa (Yukarıkızılca)'daki bir bahçede yapılmış, 10 ağacın altında ergin olmak üzere çıkış yapan son dönem nimflere ait gömlekler h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…). Cicadatra hyaline can be found in the areas of Adıyaman, Ankara, Antalya, Elazığ, Erzincan, Gümüşhane, Hakkâri, Isparta, İzmir, Konya, Kahramanmaraş, Nevşehir, Niğde, Siirt, Şanlıurfa, and Van (Kaplan & Tezcan ). Cicadivetta tibialis is vastly distributed in the surroundings of Ankara: Kalecik, Sincan and İzmir (Kaplan & Tezcan ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…). Cicadatra hyaline can be found in the areas of Adıyaman, Ankara, Antalya, Elazığ, Erzincan, Gümüşhane, Hakkâri, Isparta, İzmir, Konya, Kahramanmaraş, Nevşehir, Niğde, Siirt, Şanlıurfa, and Van (Kaplan & Tezcan ). Cicadivetta tibialis is vastly distributed in the surroundings of Ankara: Kalecik, Sincan and İzmir (Kaplan & Tezcan ).…”
Section: Resultsmentioning
confidence: 97%
“…), ecology and agricultural aspects (Gogala et al . ; Kaplan & Tezcan ; Kaplan & Tezcan ), biogeography (Sanborn ), anatomy and physiology (Sanborn ; Moulds ). However, a very limited number of studies has been reported on the extraction and physicochemical characterization of the chitin from the exoskeleton of Hemiptera species (Sajomsang & Gonil ; Chandran et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cicadatra hyalina (Fabricius, 1798) is one of the most widespread Cicadas species distributed in Azerbaijan, Turkey, Balkan Peninsula, Armenia, South Russia, Georgia, Persian, Israel, Syria, Turkmenai, Ukrain, and Jordan (Boulard et al 2018, Duffels and Laan 1985, Kartal and Zeybekoğlu 1999, Mozaffarian and Sanborn 2010, Nast 1972). According to Kaplan and Tezcan (2016), C. hyalina is recorded from Adıyaman, Ankara, Antalya, Elazığ, Erzincan, Gümüşhane, Hakkâri, Isparta, İzmir, Konya, Kahramanmaraş, Nevşehir, Niğde, Siirt, Şanlıurfa, and Van so far. In addition to these localities this species was collected from Bayburt, Burdur, Bursa, Çorum, Malatya, and Muğla provinces.…”
Section: Discussionmentioning
confidence: 99%
“…reported that studies of C. hyalina in Turkey started with Hagen (1857), Horvath (1901), Fahringer (1922), and Dlabola (1957). After then, in recent decades, Boulard (1995), Kartal and Zeybekoğlu (1999), Kaplan andTezcan (2016), andÖnder et al (2011) provided significant information about this species. However, it seems that there are still some uncertainties and deficiencies in knowledge of the C. hyalina population in Turkey.…”
mentioning
confidence: 99%